First joint observations of space weather events over Mexico - De la Luz, Victor; Gonzalez Esparza, J. Americo; Sergeeva, Maria A.; Corona Romero, Pedro; González, L. Xavier; Mejía Ambriz, Julio C.; Valdés Galicia, Jose F.; Aguilar Rodriguez, Ernesto; Rodriguez Martinez, Mario; Romero Hernández, Esmeralda; Andrade, Ernesto; Villanueva, Pablo; et al. (2018)
Abstract. The Mexican Space Weather Service (SCiESMEX in Spanish) and National Space Weather Laboratory (LANCE in Spanish) were organized in 2014 and in 2016, respectively, to provide space weather monitoring and alerts, as well as scientiﬁc research in Mexico. In this work, we presenttheresultsoftheﬁrstjointobservationsoftwoevents (22 June and 29 September 2015) with our local network of instruments and their related products. This network includes the MEXART radio telescope (solar ﬂare and radio burst), the Compact Astronomical Low-frequency, Low-cost Instrument for Spectroscopy in Transportable Observatories (CALLISTO)attheMEXARTstation(solarradioburst),the Mexico City Cosmic Ray Observatory (cosmic ray ﬂuxes), GPS receiver networks (ionospheric disturbances), and the Teoloyucan Geomagnetic Observatory (geomagnetic ﬁeld). The observations show that we detected signiﬁcant space weather effects over the Mexican territory: geomagnetic and ionospheric disturbances (22 June 2015), variations in cosmicrayﬂuxes,andalsoradiocommunications’interferences (29September2015).Theeffectsoftheseperturbationswere registered,fortheﬁrsttime,usingspaceweatherproductsby SCiESMEX:totalelectroncontent(TEC)maps,regionalgeomagneticindexKmex,radiospectrographsoflowfrequency, and cosmic ray ﬂuxes. These results prove the importance of monitoring space weather phenomena in the region and the need to strengthening the instrumentation network.